1977
DOI: 10.1104/pp.59.5.986
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Inhibition of Photosynthesis

Abstract: The magnitude of the percentage inhibition of photosynthesis by atmospheric levels of 02 in the C3 species Solanum tuberosum L., Medicago sativa L., Phaseolus vulgaris L., Glycine max L., and Triticum aestivum L. increases in a similar manner with an increase in the apparent solubility ratio of 02/CO2 in the leaf over a range of solubility ratios from 25 to 45. The solubility ratio is based on calculated levels of 02 and CO2 in the intercellular spaces of leaves as derived from whole (1,5,11,12,14,15,18,22 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(39 citation statements)
references
References 19 publications
3
35
1
Order By: Relevance
“…The ratio of the solubilities of O 2 and CO 2 increase with temperature and Ku and Edwards (1977) have suggested that photorespiration increases more rapidly with temperature than does carboxylation for this reason. If the fugacities of the substances are the relevant thermodynamic measures (Badger and Collatz 1977) then to the extent that O z and CO2 act as perfect gases the fugacities are identical with the partial pressures and not affected by their solubilities.…”
Section: Temperaturementioning
confidence: 99%
“…The ratio of the solubilities of O 2 and CO 2 increase with temperature and Ku and Edwards (1977) have suggested that photorespiration increases more rapidly with temperature than does carboxylation for this reason. If the fugacities of the substances are the relevant thermodynamic measures (Badger and Collatz 1977) then to the extent that O z and CO2 act as perfect gases the fugacities are identical with the partial pressures and not affected by their solubilities.…”
Section: Temperaturementioning
confidence: 99%
“…The temperature dependence of the ratio of photosynthesis to photorespiration has been attributed to the kinetic properties of ribulose bisphosphate carboxylase oxygenase (RuBPCO) (Laing, Ogren, and Hageman, 1974;Badger and Collatz, 1978) and to a change in the solubility ratio of CO 2 to O 2 (Ku and Edwards, 1977a). The ratio of carboxylase to oxygenase of RuBPCO has been characterized by the CO 2 /O 2 specificity factor (S) (Laing et al y 1974;Jordan and Ogren, 1981): Exchange where V c and V o are maximal velocities of carboxylation and oxygenation, v c and v 0 are velocities of both reactions, K c and K o are Michaelis constants for CO 2 and O 2 respectively, and 0 and C are concentrations of O 2 and CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It has likewise become apparent that suggested simplifications of these kinetic equations may heavily bias results. Although Ku and Edwards (12,13) To describe a particular set of data, it is necessary to determine the values of five parameters: RM, the diffusion resistance from the intercellular air space to the fixation site; Kc, the leaf affinity coefficient for CO2 in CO2 fixation; Ko2, the leaf affinity coefficient for 02 in oxygenation (photorespiration based on the rate of CO2 evolution); PM, the maximum rate of CO2 fixation at saturating C02; and WM, the maximum rate of oxygenation at saturating 02. It may be possible in the future to relate the leaf affinity coefficient for CO2 more closely to biochemical kinetics (cf.…”
mentioning
confidence: 99%
“…The objective of this paper is to reevaluate the conclusions of Ku and Edwards (12,13) using an alternative analysis. This second interpretation explains the original data but may lead to very different conclusions, which are fundamental to understanding the photosynthetic response of whole plant leaves to environmental factors.…”
mentioning
confidence: 99%